MEMBANGUN JEMBATAN GENERASI: PROGRAM FELLOWSHIP INTERGENERASI UNTUK MENINGKATKAN KEBERSAMAAN USIA EMAS DAN ANAK MUDA DI GEREJA BETHEL IINDONESIA BATAM CENTER - Suryady, Robertus; Samosir, Gom Harrys; Suhendra, Suhendra (JURNAL BEATITUDES, 2025)
The aim of this paper is to understand the important role of enhancing intergenerational fellowship programmes to improve the interaction between the golden age generation and young people. Interaction between young people and the golden age generation has many benefits: Natural mentorship, mutual understanding, improved mental and social health: Elders who interact with young people tend to be happier and feel valued. This programme is designed with the following main objectives: to build closer relationships between youth and elders in the church, to increase understanding and respect between generations, to create opportunities for sharing experiences and spiritual wisdom, to encourage active participation of the golden age generation in the life of the church.